Ultrasound findings of the thyroid gland in technical staff occupationally exposed and not exposed to ionizing radiations of the Hospital Central Universitario Dr. Antonio María Pineda (Boletin Médico de Postgrado, 2020)
In order to identify ultrasound findings in thyroid parenchyma of hospital staff exposed and not exposed to ionizing radiation (IR) of the Hospital Central Universitario Dr. Antonio Maria Pineda, we performed a cross-sectional descriptive study with a sample of 45 individuals exposed to IR who worked in the Servicio de Radiología y Diagnóstico por Imágenes Dr. Theoscar Sanoja Hernández and 38 individuals who worked at the Servicios de Traumatología y Ortopedia y Medicina Física y Rehabilitación and were not exposed. The results showed that 63% of the exposed group had ultrasound thyroid findings in contrast to 43% of the non-exposed group.  The most common findings in the exposed group were diffuse goiter (44%), nodules (32%) and cysts (24%) and in the non-exposed group were cysts (38%), diffuse goiter (19%) y nodules (19%).  These findings show that ultrasound thyroid findings was higher in exposed hospital staff and that the type of thyroid disease differ among both groups.
Keywords: thyroid; ionizing radiation; thyroid lesions; ultrasound findings